Implementasi Akad Musyarakah Mutaqisah Pada Pembiayaraan Kpr Di Bank Panin Dubai Syariah KC Malang - Safitri, Linda; Cahyani, Lineke Regita; Susanto, Feri; Meliza, Meza Alim; Anjaswari, Tutik (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2022)
This article aims to analyze the implementation of the musyarakah mutanaqishah contract in mortgage financing at Bank Panin Dubai Syariah KC Malang. The research method used is descriptive qualitative method by conducting interviews. The results of the analysis show that the implementation of the musyarakah mutanaqisah contract on mortgages at Bank Panin Dubai Syariah is in accordance with the DSN Fatwa Number 73/DSNMUI/XI/2008 concerning the Musyarakah Mutanaqisah Agreement, which is to cooperate between the bank and the customer to buy an asset which will then reduce ownership rights. one party through a payment mechanism. Where there is a minimum capital requirement of 20% that must be met in it.